Development of LVEP-Based IPAS Monopoly Media to Improve Nationalist Character on Grade IV Elementary School Students - Vita, Rima Widya Nugraha; Apriani, An-Nisa; Sari, Indah Perdana; Aryani, Yusinta Dwi (Journal of Islamic Education and Ethics, 2024)
The problem studied in this research is the lack of use of learning media that incorporates the Living Values Education Program (LVEP) and nationalist character by teachers, and there are still moral deviations from students, which illustrates the lack of strengthening of nationalist character. The aims of this research are 1) to produce LVEP-based IPAS monopoly media on the material "My Indonesia is Rich in Culture" to increase the character of nationalism, 2) to find out the teacher's response, 3) students' responses to the LVEP-based IPAS monopoly media on the material "My Indonesia is Rich in Culture ” to increase the character of nationalism. This type of research is Research and Development (R&D). This research uses a 4D development model. Data collection techniques in this research are observation, interviews, and questionnaires. The questionnaire in this research is in the form of a questionnaire given to one lecturer for validation by material experts who provide assessments regarding material in monopoly media. Then, one lecturer for validation was a media expert who provided an assessment regarding the media developed by the researcher. Then, the assessment was given to the class IV teacher at SDN Sambikerep to get an assessment in terms of media material and appearance. A questionnaire was given to students to find out responses regarding monopoly media. The techniques used are qualitative and quantitative. The results showed that 1) This development uses a 4D model. The validation results obtained an average score from material experts of 4.5, while the average score obtained from media experts was 4.3, with very good criteria. 2) The average score obtained from class IV teacher responses was 4.7, with criteria very good 3) Furthermore, the student's responses were positive and obtained a score percentage of 93.16%.